PKM AWARE: PENINGKATAN KESADARAN KECERDASAN BUATAN PADA SISWA MAN 1 GARUT DALAM PENGGUNAAN MEDIA SOSIAL - Rifki Nurfalah; Tri Arif Wiharso; Irman Nurichsan; Gandi Sugandi; Ginaldi Ari Nugroho (Universitas Mataram, 2026)
The development of artificial intelligence (AI) is increasingly influencing various aspects of life, including education. However, high school students' understanding of the basic concepts and uses of AI is still relatively limited. Therefore, the AWARE (Awareness of AI) Community Service Activity (PKM) was held at MAN 1 Garut on May 6, 2025. This activity aims to increase students' awareness and initial understanding of the concepts, applications, and potential of AI in supporting the learning process in the digital era. The objective of this activity is to increase students' awareness and understanding of the basic concepts of artificial intelligence (AI), examples of its applications, and the potential and challenges of utilizing AI technology in the context of secondary education. The activity method uses an educational-participatory approach through an introduction to basic AI concepts, presentation of real-world application examples, and simple demonstrations. The activity was complemented by a question-and-answer session and interactive discussion, and was evaluated through a Likert-scale-based satisfaction survey attended by 59 respondents. The evaluation results showed a very positive response from the activity participants. A total of 52.5% of respondents gave a score of 4 for the relevance of the activity topic, while 51.7% of respondents gave a score of 4 for the aspect of the activity's usefulness. In addition, 25.9% of respondents gave the highest score (5), indicating a very good level of satisfaction with the program implementation. In terms of sustainability, 96.4% of respondents expressed their willingness to continue the collaboration in the next activity. All respondents also assessed that the community service activities carried out could be implemented in the partner environment, thus indicating that the PKM AWARE program is relevant, beneficial, and has the potential for sustainable development. In conclusion, this activity successfully achieved its goal of increasing student awareness and understanding of AI and opening up opportunities for further development through learning modules and workshops for teachers.